TINJAUAN KONDISI FISIK PADA ATLET PUTERA DAN PUTERI CLUB RUMBAI BOXING CAMP PEKANBARU - Windah M M Hutapea; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Based on the author's observations at the time of carrying out observation at the club of rumbai boxing camp from the results of the above research, there are still some Boxing athletes who have physical conditions that fall into the category, the less and less. One of the factors that affect the athlete's physical condition factors i.e. Boxing workout. Based on the research that has been carried out on the athlete's physical Condition Review Prince and Princess ClubRumbai Boxing Camp Soweto, then the description data research results consists of seven types of shapes of test execution, namely: ExpandingDynamometer Test, Test, test Reach An Sit Two Hand Medicine Ball Put, Ran back and forth, Bass Test Modification. Ran 30 meters and tests Multi Fitness Test Endurance test data derived from test results multistage fitness test which was followed by a sample of as many as 5 people on Athletes Prince and Princess Tassel Club Boxing Camp Soweto, to the average value of multistage fitness test test adalah24 2, peak = 29.7, the lowest value = 20.4, median = 23.5, standard deviation = 4.10. For more details can be seen on a frequency distribution table below.Key Words: Physical Condition, The Prince And Princess Tassel Club Boxing Camp Pekanbaru